Heterogeneity of 11beta-hydroxysteroid dehydrogenase type 1/microsomal carbonyl reductase (11beta-HSD/CR) in guinea pig tissues. Purification of the liver form suggests modification in the cosubstrate binding site. - Oppermann, U; Möbus, E; Nagel, G; Maser, E (2000)
11beta-hydroxysteroid dehydrogenase (11beta-HSD) and xenobiotic carbonyl reductase activities were determined in guinea pig tissue microsomes. The data indicate the presence of a NADP(H) dependent form, distinct from the known type I isozyme. Purification of 11beta-HSD-1 from liver microsomes resulted in two distinct peaks, resolved by dye-ligand chromatography, indicating differences in the cosubstrate binding site. Immunoblot analysis using anti 11beta-HSD-1 antibodies reveals the presence of similar structural determinants between the enzyme forms. Both have an apparent molecular mass of 32 kDa, suggesting protein modifications occurring in the type 1 isozyme which account for the differences in chromatographic behaviour.